Synodality as a Style of Catholic Ecclesiology - Schmiedl, Joachim (Asian Horizons, 2020)
From the very beginning, synodality belongs to the genetics of Christianity. Ecumenical councils, regional or provincial synods, diocesan synods were held throughout the centuries. The participants were gradually reduced to bishops and clergy. A regular celebration of synods was codified for each diocese every ten years. Vatican II remembered the “venerable institutions” (CD, 36, 2). Paul VI initiated the Bishops‘ Synod as a means to inspire the Church. Synodal experiences on a national level were carried out immediately after the Council, but were suspected by Rome especially after the new Code of Canon Law 1983. Regulations for a diocesan synod were set up in 1997. In 2018 a paper of the International Theological Commission deepened in accordance with Pope Francis the notion of synodality. But its proposition of “all” participating, “a few” discussing and “one” deciding contradicts the development of synodality. Synodality is open for further developments.